KUNCI SUKSES MEMPERSIAPKAN ADMINISTRASI DAN WAWANCARA KERJA DENGAN MENGGUNNAKAN BAHASA INGGRIS DAN INDONESIA - Sudirman Sudirman; D Purnomo; Agung Edi Rustanto; Nur Haris Efendi; Rini Mardikawanty; Badriyah Badriyah (POLITEKNIK LP3I JAKARTA, 2022)
The purpose of this activity is to improve the quality of Human Resources in conducting job interviews which is the first door for someone to get a job. It is hoped that the key to successful training in preparing for administration and job interviews using English and Indonesian can improve the ability of participants in preparing the administration needed to apply for jobs and also the ability of participants to conduct job interviews using both Indonesian and English. The method used is through presentation and practice (drilling). Thus, students from State PKBM 23 Central Jakarta will gain experience on how to conduct job interviews. The results obtained in this activity are an increase in knowledge and skills regarding documents needed in the world of work and confidence in facing job interviews.Keyword : Administration, Interview, Drilling, Job